Money in “Historia monachorum in Aegypto” - Milewski, Ireneusz (Studia Ceranea, 2021)
The text discusses the accounts of money in Historia monachorum in Aegypto. There are not many of them and, in addition, they are quite succinct. The first illustrates the face of early Byzantine fiscalism, the difficulty of paying taxes, and the resulting sanctions for the insolvent debtor and his family members. The next, equally laconic, shows the nature of the business of a merchant trading his goods from Thebaid to Alexandria. The remaining analyzed information is comprised of isolated and very brief references to the issue of money in other spheres of everyday life. Historia monachorum, an important text for studying the early history of Egyptian monasticism, unfortunately, does not constitute a valuable source of information about money and the history of the economy of early Byzantium.